Examining academic landscape of mobile banking - the lens from main paths. (9th March 2020) - Chang, Hai Yen; Ma, Vincent C.; Liu, John S.; Lin, Ching-Wen
This study aims to identify trends in mobile banking (MB) research by reviewing influential academic articles. We adopted content analysis as a qualitative methodology and main path analysis as a quantitative methodology, to portray the development of MB research over the period from 1990 to 2016. We identified 14 highly influential articles in the evolution of MB literature. We found that the majority of the articles were written in an Asian context. The predominant theme shifted from MB adoption to the impact of MB on the effectiveness of individual lives. The primary concern of MB users changed from risk to usefulness, especially among the young users. The implications for financial institutions include focusing on consumer lifestyle, monitoring security measure and communicating to college students as the main potential customers.